Herkunftsbedingte und sprachliche Einflüsse bei der häuslichen Internetnutzung von Kindern - Richter, Lea; Gruchel, Nicole; Buhl, Heike M.; Kamin, Anna-Maria (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
Der Beitrag betrachtet die digitale häusliche Lernumwelt von Kindern unter besonderer Berücksichtigung der Differenzkategorien Herkunft und Sprache und erarbeitet Zusammenhänge zwischen dem Migrationshintergrund, der Familiensprache, einer internetbezogenen Eltern-Kind-Interaktion sowie einer unterhaltungs- und schulbezogenen Nutzung des Internets von Kindern. Empirische Grundlagen sind standardisierte Eltern- und Kinderbefragungen sowie ethnografisch orientierte Untersuchungen in Familien. Die quantitativen Analysen zeigen, dass Kinder, deren Hauptverkehrssprache in der Familie nicht Deutsch ist, häufiger gemeinsam mit ihren Eltern das Internet nutzten. Vertiefend liessen in der qualitativen Untersuchung diejenigen Kinder häufigere und komplexere Internetnutzungsformen für schulische Zwecke erkennen, die einen Migrationshintergrund aufweisen und hauptsächlich in ihrer Herkunftssprache (nicht Deutsch) innerhalb der Familie sprechen. Insbesondere in Familien, die selten in der Häuslichkeit Deutsch sprechen, hat sich die (gemeinsame) Internetrecherche als Mittel zur Kompensation von Sprachbarrieren erwiesen. Fehlende elterliche Unterstützungsmöglichkeiten aufgrund von sprachlichen Verständnisproblemen können insofern durch kindliche, elterliche oder gemeinsame Rechercheprozesse ausgeglichen werden.
Keywords: General Medicine

Adding Why to What? Analyses of an Everyday Explanation - Terfloth, Lutz; Schaffer, Michael; Buhl, Heike M.; Schulte, Carsten
In XAI it is important to consider that, in contrast to explanations for professional audiences, one cannot assume common expertise when explaining for laypeople. But such explanations between humans vary greatly, making it difficult to research commonalities across explanations. We used the dual nature theory, a techno-philosophical approach, to cope with these challenges. According to it, one can explain, for example, an XAI's decision by addressing its dual nature: by focusing on the Architecture (e.g., the logic of its algorithms) or the Relevance (e.g., the severity of a decision, the implications of a recommendation). We investigated 20 game explanations using the theory as an analytical framework. We elaborate how we used the theory to quickly structure and compare explanations of technological artifacts. We supplemented results from analyzing the explanation contents with results from a video recall to explore how explainers justified their explanation. We found that explainers were focusing on the physical aspects of the game first (Architecture) and only later on aspects of the Relevance. Reasoning in the video recalls indicated that EX regarded the focus on the Architecture as important for structuring the explanation initially by explaining the basic components before focusing on more complex, intangible aspects. Shifting between addressing the two sides was justified by explanation goals, emerging misunderstandings, and the knowledge needs of the explainee. We discovered several commonalities that inspire future research questions which, if further generalizable, provide first ideas for the construction of synthetic explanations.

Chemical and photophysical properties of amine functionalized bis‐NHC‐pyridine‐Ru(II) complexes - Fritsch, Lorena; Vukadinovic, Yannik; Lang, Moritz; Naumann, Robert; Bertrams, Maria-Sophie; Kruse, Ayla; Schoch, Roland; Müller, Patrick; Neuba, Adam; Dierks, Philipp; Lochbrunner, Stefan; Kerzig, Christoph; et al. (ChemPhotoChem)
The effects of backbone amine functionalization in three new homoleptic C^N^C type ruthenium(II) complexes bearing a tridentate bis‐imidazole‐2‐ylidene pyridine ligand framework are characterized and studied by single crystal diffraction, electrochemistry, optical spectroscopy and transient absorption spectroscopy in combination with ab initio DFT calculations. Functionalization by dimethylamine groups in 4‐position of the pyridine backbone significantly influences the properties of the complexes as revealed by comparison with the unfunctionalized references. As a result of the amine functionalization, a higher molar absorption coefficient of the MLCT bands, a decreased photoluminescence quantum yield at room temperature together with a shortened excited state lifetime but an improved photostability is observed. Introduction of electron donating and withdrawing groups at the NHC unit modifies the electronic and optical properties, such as the oxidation potential, absorption and emission properties, and the lifetimes of the excited states.
Keywords: Photo

Iron(III)-Complexes with N-Phenylpyrazole-Based Ligands - Hirschhausen, Tanja; Fritsch, Lorena; Lux, Franziska; Steube, Jakob; Schoch, Roland; Neuba, Adam; Egold, Hans; Bauer, Matthias (Inorganics)
The use of iron as a replacement for noble metals in photochemical and photophysical applications is challenging due to the typically fast deactivation of short-lived catalytically active states. Recent success of a cyclometalated iron(III) complex utilizing a bis-tridentate ligand motif inspired the use of phenyl-1H-pyrazole as a bidentate ligand. Five complexes using the tris(1-phenylpyrazolato-N,C2)iron(III) complex scaffold are presented. In addition to the parent complex, four derivatives with functionalization in the meta-position of the phenyl ring are thoroughly investigated by single crystal diffractometry, UV-Vis-spectroscopy, and cyclic voltammetry. Advanced X-ray spectroscopy in the form of X-ray absorption and emission spectroscopy allows unique insights into the electronic structure as well as DFT calculations. The ligand design leads to overlapping MLCT and LMCT absorption bands, and emissive behavior is suppressed by low-lying MC states.
Keywords: Photo

High‐Resolution X‐ray Absorption and Emission Spectroscopy for Detailed Analysis of New CO2 Methanation Catalysts - Strübbe, Sven; Nowakowski, Michał; Schoch, Roland; Bauer, Matthias (ChemPhysChem)
Abstract A new approach for the characterization of CO 2 methanation catalysts prepared by thermal decomposition of a nickel MOF by hard X‐ray photon‐in/photon‐out spectroscopy in form of high energy resolution fluorescence detected X‐ray absorption near edge structure spectroscopy (HERFD‐XANES) and valence‐to‐core X‐ray emission (VtC‐XES) is presented. In contrast to conventional X‐ray absorption spectroscopy, the increased resolution of both methods allows a more precise phase determination of the final catalyst, which is influenced by the conditions during MOF decomposition.
Keywords: Catalysis

Structural transitions during Ni nanoparticle formation by decomposition of a Ni-containing metal-organic framework using in-situ total scattering - Prinz, Nils; Strübbe, Sven; Bauer, Matthias; Zobel, Mirijam (New Journal of Chemistry)
For improved and rational design of catalysts, in-depth knowledge of their formation and structural evolution during synthesis is a key parameter. Thus, preparation of a Ni methanation catalyst derived from...
Keywords: Catalysis

Ultrafast two-colour X-ray emission spectroscopy reveals excited state landscape in a base metal dyad - Bauer, Matthias

Geschlechterspezifische Effekte in der bewegungstherapeutischen Behandlung von hämodynamischen Regulationsstörungen bei Morbus Parkinson - Siche-Pantel, Franziska; Jakobsmeyer, Rasmus; Buschfort, Rüdiger; Mühlenberg, Manfred; Michels, Heinke; Oesterschlink, Julian; Reinsberger, Claus (B&G Bewegungstherapie und Gesundheitssport)
Zusammenfassung Einleitung Motorische Symptome bei Morbus Parkinson lassen sich durch körperliche Aktivität modifizieren. Inwiefern dies auch für nicht-motorische, autonome Symptome gilt, ist weitaus weniger bekannt. Die Erkrankung weist zudem eine Vielzahl an geschlechterspezifischen Unterschieden auf. Epidemiologische Untersuchungen deuten zum Beispiel auf einen besseren primärpräventiven Effekt durch körperliche Aktivität bei Männern als bei Frauen hin. Daten zu geschlechterspezifischen Effekten auf das autonome Nervensystem sind jedoch limitiert. Im Rahmen der vorliegenden Pilotstudie sollen mögliche geschlechterspezifische Effekte einer Bewegungsintervention auf Störungen der hämodynamischen Regulation als Manifestation nicht-motorischer Symptome untersucht werden. Diese sind aufgrund ihrer oft gegensätzlichen hypo- und hypertonen Ausprägung schwierig medikamentös zu behandeln, lassen sich aber gegebenenfalls durch Bewegungsinterventionen modifizieren. Methodik Bei 42 Patienten und Patientinnen (Alter: 70,3 Jahre; 24 Männer; 18 Frauen) wurden vor und nach einer mehrwöchigen, stationären Parkinsonkomplexbehandlung hämodynamische Parameter in einem Schellongtest untersucht. Mittels anschließender Regressionsanalyse erfolgte eine Quantifizierung der Abhängigkeit von den Faktoren Alter, Body Mass Index, Krankheitsdauer, Vorerkrankungen, Sitzendblutdruck und hypotensiv wirkender Medikamente. Ergebnis Bei 44% der Männer und 46% der Frauen traten hämodynamische Regulationsstörungen im Stand und in Rückenlage mindestens einmal auf. Eine vor Therapiebeginn präsentierte Regulationsstörung im Stand zeigte sich in keiner Geschlechtergruppe durch die Parkinsonkomplexbehandlung verändert. Frauen zeigten zu Therapieende jedoch einen signifikant niedrigeren Blutdruck im Liegen (p=0,022*). Unabhängig von der Komplextherapie fiel der Blutdruck in Rückenlage bei Frauen nach Orthostasebelastung höher aus als davor (vor Therapie: p=0,015 *; nach Therapie: p=0,021*). Jedes Lebensjahr erhöhte das Risiko für eine hämodynamische Regulationsstörung in Rückenlage in der Gesamtgruppe um 12,4% (Regressionskoeffizient B=0,117; p=0,014 *; Exp(B)=1,124). Schlussfolgerung Systematische Effekte auf Blutdruckwerte im Rahmen von Orthostasereaktionen durch eine Parkinsonkomplexbehandlung konnten nicht nachgewiesen werden. Allerdings zeigte sich bei Frauen nach Parkinsonkomplexbehandlung eine Senkung der Blutdruckwerte in Rückenlage. Das scheinbar unsystematische, teils geschlechterspezifische Auftreten hämodynamischer Regulationsstörungen fordert ein individualmedizinisch angelegtes Vorgehen im therapeutischen Alltag.
Keywords: General Medicine

Nächtliche sympathische Aktivität und subjektive Symptome nach sport-assoziierter Concussion: eine Pilotstudie - Delling, Anne Carina; Jakobsmeyer, Rasmus; Christiansen, Nele; Coenen, Jessica; Reinsberger, Claus (B&G Bewegungstherapie und Gesundheitssport)
Zusammenfassung Einleitung Eine sport-assoziierte Concussion (saC) ist eine oftmals unterschätzte Hirnverletzung, die vor allem in Kontakt- und Kollisionssportarten häufig vorkommt. SaCs können zu einer Vielzahl an klinischen Symptomen führen. Akute und zum Teil die klinische Regeneration überdauernde parasympathische Inhibierung im Autonomen Nervensystem (ANS) wurde nach saC bereits häufig beschrieben. Über Veränderungen im sympathischen Nervensystem ist jedoch noch wenig bekannt. Diese wurden durch Messungen der elektrodermalen Aktivität (EDA) im Schlaf, der erheblich zur Regeneration nach saC beiträgt, sowie im Zusammenhang mit subjektiven Symptomen nach saC im Rahmen einer Pilotstudie untersucht. Methode 18 Sportler und Sportlerinnen mit diagnostizierter saC und 18 nach Alter, Geschlecht, Größe, Gewicht, Sportart und Leistungsklasse gematchte Kontrollathleten und -athletinnen trugen in den Nächten während der individuellen Return-to-Sport (RTS) Phase sowie drei Wochen nach Abschluss des RTS (postRTS) einen Handgelenkssensor (E4 Empatica Inc., Mailand, Italien). Anteile nächtlicher tonischer (meanEDA) und phasischer (EDRs, Schlafstürme) EDA wurden zwecks Gruppenvergleich ermittelt und mit saC-Symptomen (SCAT5) sowie dem subjektiven Erholungszustand nach Schlaf mittels Mann-Whitney U-Tests oder ungepaarten t-Tests verglichen. Ergebnisse Während und nach dem RTS konnten keine Gruppenunterschiede in den nächtlichen EDA-Parametern nachgewiesen werden. Eine höhere meanEDA während des RTS korrelierte mit einer höheren Anzahl an Symptomen (p=0,025, r=0,525) und eine erhöhte phasische EDA mit einem geringeren Anstieg des subjektiven Erholungszustands von vor zu nach Schlaf (EDRs: p=0,007, r=−0,642; EDRs/min: p>0,001, r=−0,762; Schlafstürme: p=0,011, r=−0,616). Fazit Die nächtliche EDA nach saC unterschied sich während und nach dem RTS nicht signifikant zu gematchten Kontrollsportlern und -sportlerinnen. Der Zusammenhang zwischen höherer EDA während des RTS und der Anzahl an saC-Symptomen sowie der geringeren subjektiven Erholung nach Schlaf könnte sowohl ursächlich für als auch Effekt der subjektiven Symptome sein und sollte durch Baseline-Messungen und in Kombination mit parasympathischen Markern künftig weiter untersucht werden.
Keywords: General Medicine

Home-Based Measurements of Nocturnal Cardiac Parasympathetic Activity in Athletes during Return to Sport after Sport-Related Concussion - Delling, Anne Carina; Jakobsmeyer, Rasmus; Coenen, Jessica; Christiansen, Nele; Reinsberger, Claus (Sensors)
Sport-related concussions (SRC) are characterized by impaired autonomic control. Heart rate variability (HRV) offers easily obtainable diagnostic approaches to SRC-associated dysautonomia, but studies investigating HRV during sleep, a crucial time for post-traumatic cerebral regeneration, are relatively sparse. The aim of this study was to assess nocturnal HRV in athletes during their return to sports (RTS) after SRC in their home environment using wireless wrist sensors (E4, Empatica, Milan, Italy) and to explore possible relations with clinical concussion-associated sleep symptoms. Eighteen SRC athletes wore a wrist sensor obtaining photoplethysmographic data at night during RTS as well as one night after full clinical recovery post RTS (>3 weeks). Nocturnal heart rate and parasympathetic activity of HRV (RMSSD) were calculated and compared using the Mann–Whitney U Test to values of eighteen; matched by sex, age, sport, and expertise, control athletes underwent the identical protocol. During RTS, nocturnal RMSSD of SRC athletes (Mdn = 77.74 ms) showed a trend compared to controls (Mdn = 95.68 ms, p = 0.021, r = −0.382, p adjusted using false discovery rate = 0.126) and positively correlated to “drowsiness” (r = 0.523, p = 0.023, p adjusted = 0.046). Post RTS, no differences in RMSSD between groups were detected. The presented findings in nocturnal cardiac parasympathetic activity during nights of RTS in SRC athletes might be a result of concussion, although its relation to recovery still needs to be elucidated. Utilization of wireless sensors and wearable technologies in home-based settings offer a possibility to obtain helpful objective data in the management of SRC.
Keywords: Electrical and Electronic Engineering; Biochemistry; Instrumentation; Atomic and Molecular Physics; and Optics; Analytical Chemistry

Umsetzung einer optimierten Oberflächenschlitzung zur Wirbelstromverlustreduktion auf der Oberfläche eines additiv gefertigten Permanentmagnet-Rotors - Haase, Michael; Bieber, Maximilian; Tasche, Frederik; Schaper, Mirko; Hoyer, Kay-Peter; Ponik, Bernd; Magyar, Balázs (Proceedings of the 19th Rapid.Tech 3D Conference Erfurt, Germany, 9–11 May 2023)

Was ist eine Interpretationsedition? - Münzmay, Andreas; Berndt, Axel

TemporalFC: A Temporal Fact Checking approach over Knowledge Graphs - Qudus, Umair; Röder, Michael; Kirrane, Sabrina; Ngonga Ngomo, Axel-Cyrille (The Semantic Web – ISWC 2023)
Verifying assertions is an essential part of creating and maintaining knowledge graphs. Most often, this task cannot be carried out manually due to the sheer size of modern knowledge graphs. Hence, automatic fact-checking approaches have been proposed over the last decade. These approaches aim to compute automatically whether a given assertion is correct or incorrect. However, most fact-checking approaches are binary classifiers that fail to consider the volatility of some assertions, i.e., the fact that such assertions are only valid at certain times or for specific time intervals. Moreover, the few approaches able to predict when an assertion was valid (i.e., time-point prediction approaches) rely on manual feature engineering. This paper presents T EMPORAL FC, a temporal fact-checking approach that uses multiple sources of background knowledge to assess the veracity and temporal validity of a given assertion. We evaluate T EMPORAL FC on two datasets and compare it to the state of the art in fact-checking and time-point prediction. Our results suggest that T EMPORAL FC outperforms the state of the art on the fact-checking task by 0.13 to 0.15 in terms of Area Under the Receiver Operating Characteristic curve and on the time-point prediction task by 0.25 to 0.27 in terms of Mean Reciprocal Rank. Our code is open-source and can be found at https://github.com/dice-group/TemporalFC.
Keywords: knowgraphs enexa sail nebulaproject dice ngonga saleem roeder qudus

Does listener gaze in face-to-face interaction follow the Entropy Rate Constancy principle: An empirical study - Wang, Yu; Buschmeier, Hendrik (Findings of the Association for Computational Linguistics: EMNLP 2023)
It is generally assumed that language (written and spoken) follows the entropy rate constancy (ERC) principle, which states that the information density of a text is constant over time. Recently, this has also been found for nonverbal gestures used in monologue, but it is still unclear whether the ERC principle also applies to listeners' nonverbal signals. We focus on listeners' gaze behaviour extracted from video-recorded conversations and trained a transformer-based neural sequence model to process the gaze data of the dialogues and compute its information density. We also compute the information density of the corresponding speech using a pre-trained language model. Our results show (1) that listeners' gaze behaviour in dialogues roughly follows the ERC principle, as well as (2) a congruence between information density of speech and listeners' gaze behaviour.

Scaffolding the human partner by contrastive guidance in an explanatory human-robot dialogue - Groß, André; Singh, Amit; Banh, Ngoc Chi; Richter, Birte; Scharlau, Ingrid; Rohlfing, Katharina J.; Wrede, Britta (Frontiers in Robotics and AI)
Explanation has been identified as an important capability for AI-based systems, but research on systematic strategies for achieving understanding in interaction with such systems is still sparse. Negation is a linguistic strategy that is often used in explanations. It creates a contrast space between the affirmed and the negated item that enriches explaining processes with additional contextual information. While negation in human speech has been shown to lead to higher processing costs and worse task performance in terms of recall or action execution when used in isolation, it can decrease processing costs when used in context. So far, it has not been considered as a guiding strategy for explanations in human-robot interaction. We conducted an empirical study to investigate the use of negation as a guiding strategy in explanatory human-robot dialogue, in which a virtual robot explains tasks and possible actions to a human explainee to solve them in terms of gestures on a touchscreen. Our results show that negation vs. affirmation 1) increases processing costs measured as reaction time and 2) increases several aspects of task performance. While there was no significant effect of negation on the number of initially correctly executed gestures, we found a significantly lower number of attempts—measured as breaks in the finger movement data before the correct gesture was carried out—when being instructed through a negation. We further found that the gestures significantly resembled the presented prototype gesture more following an instruction with a negation as opposed to an affirmation. Also, the participants rated the benefit of contrastive vs. affirmative explanations significantly higher. Repeating the instructions decreased the effects of negation, yielding similar processing costs and task performance measures for negation and affirmation after several iterations. We discuss our results with respect to possible effects of negation on linguistic processing of explanations and limitations of our study.
Keywords: Artificial Intelligence; Computer Science Applications

Gelingensbedingungen gestaltungsorientierter Schulentwicklung - Schwabl, Franziska; Daniel-Söltenfuß, Desiree (Organisation zwischen Theorie und Praxis)

RELD: A Knowledge Graph of Relation Extraction Datasets - Manzoor, Ali; Saleem, Muhammad; Moussallem, Diego; Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (The Semantic Web)

iPDP: On Partial Dependence Plots in Dynamic Modeling Scenarios - Muschalik, Maximilian; Fumagalli, Fabian; Jagtani, Rohit; Hammer, Barbara; Huellermeier, Eyke (Proceedings of the World Conference on Explainable Artificial Intelligence (xAI))

iSAGE: An Incremental Version of SAGE for Online Explanation on Data Streams - Muschalik, Maximilian; Fumagalli, Fabian; Hammer, Barbara; Huellermeier, Eyke (Machine Learning and Knowledge Discovery in Databases: Research Track - European Conference (ECML PKDD))

On Feature Removal for Explainability in Dynamic Environments - Fumagalli, Fabian; Muschalik, Maximilian; Hüllermeier, Eyke; Hammer, Barbara (Proceedings of the European Symposium on Artificial Neural Networks (ESANN))